Prevalence of acute and chronic viral seropositivity and characteristics of disease in patients with psoriatic arthritis treated with cyclosporine: a post hoc analysis from a sex point of view on the observational study of infectious events in psoriasis complicated by active psoriatic arthritis - Colombo D; Chimenti S; Grossi PA; Marchesoni A; Bardazzi F; Ayala F; Simoni L; Vassellatti D; Bellia G (Dove Medical Press, 2015)
Delia Colombo,1 Sergio Chimenti,2 Paolo Antonio Grossi,3 Antonio Marchesoni,4 Federico Bardazzi,5 Fabio Ayala,6 Lucia Simoni,7 Donatella Vassellatti,1 Gilberto Bellia1 On behalf of SYNERGY Study Group 1Novartis Farma Italia, Origgio (VA), 2Tor Vergata Polyclinic Rome, 3Macchi Hospital and Foundation, Varese, 4Orthopaedic Institute Pini, Milan, 5S Orsola-Malpighi Polyclinic, Bologna, 6University Federico II Naples, 7MediData srl, Modena, Italy Background: Sex medicine studies have shown that there are sex differences with regard to disease characteristics in immune-mediated inflammatory diseases, including psoriasis, in immune response and susceptibility to viral infections. We performed a post hoc analysis of the Observational Study of infectious events in psoriasis complicated by active psoriatic arthritis (SYNERGY) study in patients with psoriatic arthritis (PsA) treated with immunosuppressive regimens including cyclosporine, in order to evaluate potential between-sex differences in severity of disease and prevalence of viral infections.Methods: SYNERGY was an observational study conducted in 24 Italian dermatology clinics, which included 238 consecutively enrolled patients with PsA, under treatment with immunosuppressant regimens including cyclosporin A. In this post hoc analysis, patients' demographical data and clinical characteristics of psoriasis, severity and activity of PsA, prevalence of seropositivity for at least one viral infection, and treatments administered for PsA and infections were compared between sexes.Results: A total of 225 patients were evaluated in this post hoc analysis, and 121 (54%) were males. Demographic characteristics and concomitant diseases were comparable between sexes. Statistically significant sex differences were observed at baseline in Psoriasis Area and Severity Index score (higher in males), mean number of painful joints, Bath Ankylosing Spondylitis Disease Activity Index, and the global activity of disease assessed by patients (all higher in females). The percentage of patients with at least one seropositivity detected at baseline, indicative of concomitant or former viral infection, was significantly higher among women than among men. No between-sex differences were detected in other measures, at other time points, and in treatments. Patients developed no hepatitis B virus or hepatitis C virus reactivation during cyclosporine treatment.Conclusion: Our post hoc sex analysis suggests that women with PsA have a greater articular involvement and a higher activity of disease compared to males. Immunosuppressive treatment with cyclosporine seems not to increase susceptibility to new infections or infectious reactivations, with no sex differences. Keywords: psoriatic arthritis, sex, viral infections, SYNERGY, cyclosporine